ANALYSIS OF THE HADITH NARRATED BY ABU HURAIRAH ON PURIFYING THE TRACE OF A DOG'S LICK (PERSPECTIVES OF THE FOUR SCHOOLS OF THOUGHT AND CHEMISTRY) - Alambudi, Muhammad Sutan; Firdaus, Ahmad; Akhnaf, Muhammad; Kholik, Jamaluddin Acmad (Jurnal Studi Hadis Nusantara, 2025)
This research discusses the hadith narrated by Abu Hurairah, which states that the way to purify a vessel that a dog has licked is to wash it seven times, one of which should involve using soil. This hadith serves as the basis for Islamic law in determining najis mughallazah (severe impurity) and its purification methods. However, there are differing opinions among the four schools of Islamic jurisprudence (Hanafi, Maliki, Shafi'i, and Hanbali) regarding the number and method of washing. This study also conducts a meta-analysis of the effectiveness of clay-based soap as an alternative cleaner for dog najis in a modern context. The research methodology employed is qualitative with a descriptive-analytical approach. Data were collected through literature studies involving hadith texts, the views of scholars from the four schools, and findings from modern chemical research. The results indicate that the Shafi'i and Hanbali schools require washing seven times with one wash using soil, while the Hanafi school states that three washes are sufficient without the obligation to use soil. Meanwhile, the Maliki school asserts that dog saliva is not najis, but it is still recommended to wash seven times as an act of obedience to religious law. From a chemical perspective, soil has been proven to have the ability to absorb impurities and kill bacteria, such as Capnocytophaga and Pasteurella found in dog saliva.